The Profile of Physical Activity in Children Surviving Acute Lymphoblastic Leukemia based on the Global Physical Activity Questionnaire in Surakarta - Zahara, Dini Safitri; Riza, Muhammad; Nugroho, Hari Wahyu (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Acute lymphoblastic leukemia is one of the most common malignancies in children with the highest incidence aged 3-7 years. Management and treatments such as chemotherapy and radiotherapy have musculoskeletal and neuromuscular side effects which can significantly reduce the physical activity of leukemia patients and survivors. This study aims to determine the profile of the physical activity level of children with acute lymphoblastic leukemia as assessed by the Global Physical Activity Questionnaire (GPAQ) in Surakarta, Indonesia. Subjects and Method: This was a study with a cross-sectional design. Children who survived acute lymphoblastic leukemia who had completed chemotherapy at Dr. Moewardi Hospital and met the inclusion criteria were included in this study. A sample of 26 patients was selected through purposive sampling. Demographic data were obtained through interviews and the profile of the patient's physical activity level was assessed using the GPAQ questionnaire. Data analysis was performed using a Pearson Correlation test with SPSS 22.0. Results: The total sample in this study was 26 children with acute lymphoblastic leukemia. As many as 11.5% of children with acute lymphoblastic leukemia experienced decreased physical activity. There was a significant relationship between length of stay (p=0.001), age (p=0.004), gender (p=0.031), and the degree of risk of acute lymphoblastic leukemia (p=0.004) with the category of physical activity based on the GPAQ score. Conclusion: As many as 11.5% of children with acute lymphoblastic leukemia experienced decreased physical activity. The length of time being a survivor, the degree of risk of acute lymphoblastic leukemia, the age of the survivor, and gender are risk factors for decreased physical activity in children.